Conformation-dependent phosphorylation of p53 - Adler, Victor (The National Academy of Sciences of the USA, 1997)
Phosphorylation of the p53 tumor suppressor protein is known to modulate its functions. Using bacterially produced glutathione S-transferase (GST)-p53 fusion protein and baculovirus-expressed histidine-tagged p53 ((His)p53), we have determined human p53 phosphorylation by purified forms of jun-N-kinase (JNK), protein kinase A (PKA), and β subunit of casein kinase II (CKIIβ) as well as by kinases present in whole cell extracts (WCEs). We demonstrate that PKA is potent p53 kinase, albeit, in a conformation- and concentration-dependent manner, as concluded by comparing full-length with truncated forms of p53. We further demonstrate JNK interaction with GST-p53 and the ability of JNK to phosphorylate truncated forms of GST-p53 or full-length (His)p53. Dependence of phosphorylation on conformation of p53 is further supported by the finding that the wild-type form of p53 (p53(wt)) undergoes better phosphorylation by CKIIβ and by WCE kinases than mutant forms of p53 at amino acid 249 (p53(249)) or 273 (p53(273)). Moreover, shifting the kinase reaction’s temperature from 37°C to 18°C reduces the phosphorylation of mutant p53 to a greater extent than of p53(wt). Comparing truncated forms of p53 revealed that the ability of CKIIβ, PKA, or WCE kinases to phosphorylate p53 requires amino acids 97–155 within the DNA-binding domain region. Among three 20-aa peptides spanning this region we have identified residues 97–117 that increase p53 phosphorylation by CKIIβ while inhibiting p53 phosphorylation by PKA or WCE kinases. The importance of this region is further supported by computer modeling studies, which demonstrated that mutant p53(249) exhibits significant changes to the conformation of p53 within amino acids 97–117. In summary, phosphorylation-related analysis of different p53 forms in vitro indicates that conformation of p53 is a key determinant in its availability as a substrate for different kinases, as for the phosphorylation pattern generated by the same kinase.